Resilience of the Copepod Oithona similis to Climatic Variability: Egg Production, Mortality, and Vertical Habitat Partitioning - Cornwell, Louise Elisabeth; Fileman, Elaine S.; Bruun, John T.; Hirst, Andrew Garwood; Tarran, Glen Adam; Findlay, Helen S.; Lewis, Ceri; Smyth, Timothy James; McEvoy, A. J.; Atkinson, A. (Frontiers in Marine Science, 2020)
There has been an overall decline in copepod populations across the North Atlantic over the past few decades. Reasons for these declines are unclear, and several major species, including the cyclopoid copepod Oithona similis, have maintained stable populations at station L4 in the western English Channel. To identify the factors contributing to this stability, we conducted a one-year intensive study of O. similis at L4 over 2017-2018, a period of high climatic variability. For context, dominant frequency state analysis was applied to the 30-year L4 time series to derive the baseline dynamics of the Oithona spp. population. The Oithona spp. baseline demonstrated stable densities and a bimodal annual cycle. These dynamics, as well as those of reproductive output and phenological timings, were upheld in 2017-2018, indicating resilience to climatic variability. During 2017-2018, all life stages of O. similis were relatively scarce in the top 2 m of the water column, despite the presence of abundant food. Naupliar stages occurred predominantly around 10 m depth, with subsequent life stages progressively deeper. We suggest this vertical structuring may represent different trade-offs between feeding and mortality risk between ontogenetic stages. To determine the traits that contribute to population stability, we compare O. similis with the large, biomass-dominant copepod, Calanus helgolandicus. Despite having contrasting functional traits, both species have exhibited strong population stability over the time series. Our results provide evidence that mortality plays a major role in maintaining population dynamics.